Glorious science or “dead dog”? Jean de Jandun and the quarrel over astrology in fourteenth-century Paris - Nothaft, CPE (Brill Academic Publishers, 2019)
This article edits and examines a little-known epistolary treatise datable to 1322, which survives in a fifteenth-century manuscript in the Herzog-August-Bibliothek, Wolfenbüttel. The author of this work was engaged in a heated argument with the Parisian philosopher Jean de Jandun over the status and rationality of astrology. Jean’s pro-astrological stance is documented in a letter dated 28 October 1321, which survives for having been appended to the main treatise. In responding to Jean de Jandun’s letter, the author delivered a trenchant critique of astrology grounded almost entirely in philosophical, as opposed to theological, ideas, addressing issues such as empirical evidence, causality, and contingency. The author’s way of pointing out ruptures between astrology and Aristotelian natural philosophy marks him out as an intellectual precursor to the much better-known anti-astrological polemics written later in the same century by Parisian thinkers such as Nicole Oresme and Heinrich von Langenstein.